Obesidad en el embarazo y sus complicaciones en pacientes atendidas en el Centro de Salud Universitario de Motupe - Armijos Peña, Shandry Daniel (2022)
Changes in eating patterns and physical activity have increased the development of maternal obesity, becoming a major public health problem, since they increase obstetric and neonatal risks, which are associated with multiple pathologies, mainly hypertensive disorders and Gestational Diabetes. The objective of this research was to establish the presence of obesity in pregnancy, determine the complications that can occur during pregnancy and relate both variables. The study was of a quantitative cross-sectional cohort type, with a sample of 246 participants, made up of 6.91% (n=17) of late-stage adolescents, while 93.09% (n=229) were young adults. It is ruled out that 78.05% (n=192) have type I obesity, 17.07% (n=42) have type II obesity, while 4.88% (n=12) patients have type III obesity. Comparing obesity and the identified complications, it was concluded that there is a statistically significant relationship between obesity and complications during pregnancy, such as infections, endocrinology, hypertensive disorders, and hematology